TRANSMEDIA STORYTELLING IN DIGITAL GAMES EXPANDING THE UNIVERSE OF ‟WARCRAFT” - CREŢU, Călin (Studia Universitatis Babeș-Bolyai Ephemerides, 2015)
The paper Transmedia storytelling in digital games is an analysis on how multiple media work in tandem to tell a story. The story analyzed is the vast universe of Warcraft, developed by Blizzard Entertainment over the last 20 years and is composed of digital games, novels, comics, manga and other products. Looking at the evolution of the game and other media products, we can observe that Blizzard Entertainment has managed to turn what initially was a trilogy of Real Time Strategy games into a story that is consumed by millions of users that play the Massively Multiplayer online role-playing game World of Warcraft, read the Warcraft novels and the Warcraft manga and comic books and will in 2016 watch the Warcraft feature movie. The present paper brings insight for game developers and media scholars on how the quality of a digital game’s story is affected when it is transformed into a transmedia storytelling product due to multiple issues that might arise. Among the issues, there is attracting new audiences as the product ages and the narrative evolves, avoiding narrative conflicts between media and managing the ideal use of storytelling techniques specific to each medium.